Earthquake Activity in the Maritime Provinces - Burke, Kenneth (Geoscience Canada, 1984)
Summary Earthquakes have been felt or reported in the Maritime Provinces for over two hundred years but it is only within the last decade that enough seismographs have been in place to detect the smaller events. In general, the epicenters of more recent earthquakes are in the same area as the larger historical earthquakes: Grand Banks, Bay of Fundy, Moncton-Dorchester area and the Central Highlands of New Brunswick, although the latter area has only been really emphasized by the Miramichi earthquakes of 1982. Values of magnitude for historical earthquakes have been reduced by basing them on felt area, rather than on maximum intensity, and there is some evidence that the epicenter of the large earthquake of 1869 in New Brunswick may have a more northerly location. Reactivation along old fault lines, concentration of stress at pluton boundaries and glacio-isostatic movements have all been offered as explanations for the cause of earth-quakes in the region. Support for all three hypotheses has been found in various studies and it is not possible at the moment to refute any of these explanations.